A construção da profissionalidade do formador de professor, atuante no contexto da formação continuada em serviço - Escanuela, Valéria Garcia de Oliveira (2020)
The teacher training is the object of study of a great number of researches in Brazil, in contrast to such datum, the teacher trainer, especially the trainer working in the continuing training in service is rarely numbered among the objects of investigation. The aforementioned reality, wedded to the researcher's professional and academic career, aroused her interest in understanding aspects of the construction of the teacher trainers’ professionality, a function that has been growing in the framework of the Departments of Education. The researcher's interest is part of the objective of this study, which can be defined as: to understand, through the investigation of social representations presented by teacher trainers working in public education networks, the aspects that are being considered by the group in the construction of their professionality. To achieve the objective, the study followed a broad path of investigation which would make it possible to contemplate different elements which such theme involves. Firstly, a wide-ranging study was carried out in partnership with the Center for International Studies on Social Representations (known in Brazil by the Portuguese acronym: NEARS). The study covered theses and dissertations that had as key words the issue of Teacher Training and Social Representations in the period between 2013 and 2018. A bibliographic review was also carried out based on: different authors, Teacher Education, Professionality and Social Representations. The previous studies have made it possible to conduct, with greater understanding, the research with teacher trainers working in two different education networks, one located in the North Region, with the participation of 31 subjects, and another in the Southeast Region, with the participation of 10 subjects, adding up to 41 trainers being listened to. The data collection method initially involved a documentary study about the Networks with the purpose of understanding the context of the teacher training policies which compose the two groups studied. In the sequence, a profile questionnaire was distributed aiming to characterize the subjects and thus, a written narrative about these teacher trainers’ scope of practice and professional career was requested. The treatment and data analysis followed the Content Analysis by Maria L. P. B. Franco and the use of the Iramuteq software with cutting in Descending Hierarchical Clustering (Portuguese acronym: CHD). The theoretical and methodological approach was based on the Theory of Social Representations with basis in Serge Moscovici's sociogenetic approach, and studies on professionality based on Marguerite Altet, Marli André, Vera Placco, José Carlos Morgado, Maria do Céu Roldão, among others. The results obtained indicate that there is an imagery construction of teacher trainers about "what to be a trainer is" and “what continuing training in service is”, such images indicate the consensual universe that defines for the subjects of our research what the professionality of the trainers is. The results will make it possible to discuss with the networks involved in the present study, how such images can be considered in teacher training programs. We know the limits of the present study; we suggest that further investigations may be carried out seeking to deepen, more and more, in the sense of understanding the shared social representations which guide the performance of teacher training groups